Clinical Features and Outcomes of Bilateral Atypical Femoral Fractures - Kosuke Hamahashi; Toshihiro Noguchi; Yoshiyasu Uchiyama; Masato Sato; Masahiko Watanabe (Case Reports in Orthopedics)
Bilateral atypical femoral fractures (AFFs) are relatively rare. In this report, we retrospectively researched clinical features and outcomes of bilateral AFFs treated at our institution. We previously treated 4 patients (8 limbs) with intramedullary nailing for complete AFFs (6 limbs) and incomplete AFFs (2 limbs). The mean age at the first operation was 53.3 years, and all patients were female. Of the 4 patients, two had breast cancer, and another two had systemic lupus erythematosus. Three of them received bisphosphonates, and 2 received denosumab, proton pump inhibitor, or glucocorticoid therapy. Only 2 of 6 cases of incomplete AFFs had prodromal pain before progressing to complete fracture. The mean interval from the first surgery to contralateral fracture or prophylactic surgery was 16 months. Radiographically, complete bone union was achieved in 6 limbs. However, a small gap at the lateral cortex of fracture site remained in 2 limbs. Finally, all of the patients were pain-free and able to walk without a cane. It is absolutely necessary to confirm contralateral femoral conditions; however, prediction of progression to complete fracture based solely on prodromal pain was difficult. Therefore, we should advise patients about the danger of progression to complete AFFs even if they are asymptomatic, and a prophylactic surgery should be performed after obtaining informed consent.